Penyebarluasan Peraturan Daerah Provinsi Kalimantan Timur Nomor 4 Tahun 2022 Tentang Fasilitasi P4GN – PNP Di Kota Samarinda: Dissemination of Kalimantan Timur Local Regulation Number 4 of 2022 Concerning Facilitation of P4GN-PNP in Samarinda City - Muslim, Ikhwanul; Mustofa, Khoirunnisak Tri; Ainun, Azmi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Community service in the form of disseminating Provincial Regulation Number 4 of 2022 regarding the Facilitation of Prevention and Eradication of Narcotics, Narcotic Precursors, and Pyschotropic Substances Abuse (P4GN-PNP) in Sungai Kungan Samarinda City, is one of the efforts by the East Kalimantan Government to impart an understanding to the community about the government’s commitment to minimizing the damage caused by drug abuse. The method of this activity involves presenting the material and conducting discussions on the latest provisions withing the regulation. One notable aspect highlighted by the participant during the dissemination of this regulation is the provision for educational institutions, both public and private, which under the jurisdiction of the Provincial Government, to accept students who have been involved in drug abuses. This serves as concrete evidence of the East Kalimantan Provincial Government’s commitment to supporting the social reintegration process for individuals involved in drug, narcotic precursor, and pyschotropic substance abuse. This initiative receives full support from the East Kalimantan Provincial Legislative Council (DPRD) with the aim of fostering a collective commitment among the residents of Samarinda City to distance themselves from all forms of drug abuses.